Transformations Used In The Process Of Translating Works From English To Uzbek (In The Example Of Daniel Gerhard Brown’s “The Da Vinci Code”) - Inog’omjonova Robiya Rustamjon qizi (Global Scientific Publishing, 2024)
This article was written based on the famous American writer Dan Brown’s work "Three Musketeers". The article analyzes the morphological, syntactic, lexical and punctuational transformations encountered during the translation of this work. For the article, literary textbooks and various Wikipediaes used in the translation process were used as reference sources.
Keywords: alliteration; parallel structure; dysphemism; oxymoron